“Untouched” Field of Folklore: The Perception of Glorified Virginity in Folk Song / Folklorun “El Değmemiş” Bölgesi: Halk Türkülerinde Yüceltilmiş Bakirelik Algısı - İsmail Abalı (Folklor/Edebiyat, 2021)
In this study, a research was conducted focusing on the perception of virginity encountered in various folkloric creations emerging within our oral tradition, especially in folk songs. As pointed out in some studies on social gender and centered on women, the phenomenon of virginity, which is one of the most soughtafter features in an unmarried woman, was investigated in detail in terms of folk songs and the problem of virginity was emphasized as a preferred feature in folk songs. In this study, which is based on written sources, including text, compiled songs from different regions of Turkey, contained about virginity encountered in the folk songs, given to the word, phrase and metaphors; the findings are presented by classification. In this regard, the perception of virginity in folk songs has been identified as the ideal wife or lover, a sign of beauty, the symbol of honor, sexual goal and a source of attraction and healing. These findings were supported with concrete examples and a general evaluation was made as well as some suggestions on the subject.